Recovery of Heavy Metals from Chrome - Plating Rinse Wastewater by Reverse Osmosis - Keethanchali, Nagaretnam (1999)
Wastewater produced by industries contains harmful and toxic metals which danger the receiving water. Chrome – plating rinse water which contains chromium is very toxic to the environment. Reverse osmosis is used with the tubular module B1 membrane to reduce the chromium, manganese, lead and copper to a reasonable level which is less harmful. Chromium (Cr) is reduced by 87.9% while Lead (Pb) is reduced by 94.3% followed by Manganese (Mn) by 85.7% and Copper (Cu) by 91.9%. the fluxrate increase with tranmembrane pressure from 43 l/m2. Hr at 40 bar 60 l/m2 with a TDS of 2689 mg/l. The permeate flux was directly proportional to the transmembrane pressure which follows the Resistance Model. This method is quite appropriate for Lead (Pb), copper (Cu) and chromium (Cr) reduction. Nowadays reverse osmosis is gaining interest in the industries which produce wastewater containing high concentration of heavy metals.